1990
DOI: 10.1097/00000658-199004000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Surgery for Morbid Obesity

Abstract: The efficacy of three gastric restriction operations were compared in a prospective randomized study of 310 morbidly obese subjects. The median patient age was 34 years (range, 18 to 62 years). They were predominantly female (13:1) and had a median pre-operative weight that was 198% of their ideal weight (range, 160% to 318%). There was an equitable dispersion of perceived risk factors between the groups under study and there were no deaths during the perioperative period. Compliance with follow-up at 3 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
0
3

Year Published

1993
1993
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(120 citation statements)
references
References 30 publications
5
112
0
3
Order By: Relevance
“…One of the RCTs that they did include used a horizontal, unbanded gastroplasty 85 and therefore should have been excluded. Four other RCTs comparing vertical banded gastroplasty with gastric bypass [86][87][88][89] as well as three retrospective series [90][91][92] and the SOS cohort trial 17 all found gastric bypass to cause greater weight loss than gastroplasty. One study not cited by either report found an equivalent weight loss between vertical banded gastroplasty and gastric bypass when patients were allowed to choose the operation, but the drop-out rate (15% seen at 5 y) was excessive.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the RCTs that they did include used a horizontal, unbanded gastroplasty 85 and therefore should have been excluded. Four other RCTs comparing vertical banded gastroplasty with gastric bypass [86][87][88][89] as well as three retrospective series [90][91][92] and the SOS cohort trial 17 all found gastric bypass to cause greater weight loss than gastroplasty. One study not cited by either report found an equivalent weight loss between vertical banded gastroplasty and gastric bypass when patients were allowed to choose the operation, but the drop-out rate (15% seen at 5 y) was excessive.…”
Section: Resultsmentioning
confidence: 99%
“…8 In contrast to the SOS study, which was almost entirely purely gastric restriction, 127 both the Washington State and Canadian studies were predominantly gastric bypass, which is associated with greater weight loss. [86][87][88][89][90][91][92] In the Canadian study, there was a 45% decrease in total health-care expenditures in the surgically treated cohort. 8 Both studies noted a significantly lower mortality in the surgical patients.…”
Section: Rcts and Levels Of Evidencementioning
confidence: 99%
“…Weight loss was 28-76 kg after 2 y, [79][80][81][82][83][84][85][86][87][88][89] 17-73 kg after 3 y, [79][80][81][86][87][88][89] and 20 kg after 8 y in one study [82][83][84] based on a completers method of analysis. No study reported the proportion of subjects with Z5% weight loss, although this was probably high given the absolute weight loss with surgical therapy.…”
Section: Surgical Therapymentioning
confidence: 99%
“…The superiority of gastric bypass over vertical banded gastroplasty in achieving weight loss has been demonstrated by several controlled studies. [24][25][26][27] Weight loss stabilizes between 18 and 24 months postsurgery; 14,28,29 a trend to regain small amounts of weight can be observed in the third year. 28 Although bariatric surgery is generally effective, there is great variability in outcome.…”
Section: Introductionmentioning
confidence: 99%